Cancer Biology: Foundations for Gastrointestinal Oncology Nursing Practice - Ibrahim, Wesam; Abu Dabbous, Aya; Kokash, Khader; Al-Maalouf, Souad; Dayah, Moath; Al-Nasri, Intisar; Al-Sadi, Fatima; Al-Nablisi, Lama; Zribi, Aref; Alzahrani, Saud; Ayaad, Omar (Asian Pacific Journal of Cancer Biology, 2025)
Background: Gastrointestinal cancers including malignancies of the colon, rectum, stomach, pancreas, liver, and esophagus represent a significant global health burden with high morbidity and mortality. Advances in molecular oncology reveal that these cancers arise through complex genetic, epigenetic, microenvironmental, and metastatic processes. Understanding these mechanisms is essential for oncology nurses to support precision medicine and deliver effective, patient-centered care. Methods: This literature review employed a structured thematic analysis to synthesize knowledge on cancer biology concepts relevant to gastrointestinal oncology nursing. Comprehensive database searches (PubMed, CINAHL, Scopus, Google Scholar) targeted publications from 2000 to 2024 addressing genetic mutations, epigenetics, tumor microenvironment, metastasis, and nursing education. Eligible articles were critically reviewed and thematically coded to identify major themes and subthemes with clinical and nursing practice relevance. Results: Three primary themes emerged: (1) Genetic and Epigenetic Alterations, including oncogene activation, tumor suppressor inactivation, microsatellite instability, and DNA methylation; (2) Tumor Microenvironment and Immune Evasion, encompassing stromal barriers, angiogenesis, immune suppression, and intercellular signaling; and (3) Mechanisms of Metastasis, detailing local invasion, epithelial-mesenchymal transition, circulation, colonization, dormancy, and reactivation. Each theme includes nursing roles in patient education, decision-making support, therapy monitoring, and psychosocial care. Conclusion: Integrating cancer biology knowledge into nursing practice is essential for anticipating patient needs, supporting shared decision-making, and managing advanced therapies in gastrointestinal oncology. Nurses must engage in ongoing education and interdisciplinary collaboration to navigate the evolving landscape of precision oncology and improve outcomes and quality of life for patients facing these complex cancers.